Synthesis, Spectral Characterization and Antimicrobial Studies of 2,3,4,5- Tetrahydroindeno-[1,2-d]-thiazolo-[3,2-a]-pyrimidine-10(H)semicarbazone Complexes of Co(II), Ni(II) and Cu(II)¶ - Rai, B.K.; Singh, Sateydev (Asian Journal of Chemistry, 2010)
A new series of transition metal complexes of Co(II), Ni(II) and Cu(II) have been synthesized from the Schiff base derived from 2,3,4,5-tetrahydroindeno-[1,2-d]-thiazolo-[3,2-a]pyrimidine- 10(H)-one. Structural features were obtained from their elemental analysis, molar conductance, Molar mass, IR, electronic spectral study and magnetic susceptibility data. Based on the stoichiometries and spectroscopic studies, the complexes have general formula [M(TITPS)2X2]; where M = Co(II), Ni(II) and Cu(II); TITPS = 2,3,4,5-tetrahydroindeno-[1,2-d]-thiazolo-[3,2- a]-pyrimidine-10(H)semicarbazone; X = Cl–, Br–, I– and NO3 –. The electronic spectral and magnetic susceptibility data of the complexes suggest an octahedral geometry around the central atom. The ligand and its complexes were tested for their antimicrobial study and antifungal screening gave good results in the presence of metal ion in the ligand system.